OP0088 The role and function of monocyte-derived fibroblast-like cells in multi-organ fibrosis in systemic sclerosis. (15th June 2017) - Rudnik, M; Stellato, M; Milleret, V; Błyszczuk, P; Maurer, B; Klingel, K; Henes, J; Sotlar, K; Ehrbar, M; Distler, O; Kania, G
Abstract : Background: Animal studies indicated bone marrow-derived cells as a source of pathological myofibroblasts in multiple organ fibrosis such as lungs, heart, skin and kidney. Monocytes are implicated in the pathogenesis of systemic sclerosis (SSc), however detailed role of specific monocyte subsets in multi-organ fibrogenesis in SSc remains unclear. Objectives: We aimed to determine the role and the contribution of circulating monocytes in the onset and progression of multi-organ fibrosis in SSc. Methods: Endomyocardial biopsies (n=10) from SSc patients and healthy controls were screened by immunohistochemistry. CD14 + monocytes isolated from peripheral blood of SSc patients and healthy donors were differentiated towards a myofibroblast phenotype by stimulation with TGF-β1, IL-4, IL-10 and IL-13. In addition, CD14 + monocytes were co-cultured in 2D and 3D models with dermal fibroblasts originating from SSc patients or healthy subjects, or with adult cardiac fibroblasts. TGF-β signalling was blocked by SD208 and A83–01 inhibitors. Profibrotic gene expression and protein secretion were evaluated by qPCR, Western blot, protein array, immunofluorescence and ELISA. Results: The myocardia of SSc patients revealed the presence of CD45-expressing infiltrates, an extended collagen I deposition and the presence of CD14-expressing elongated cells in the fibrotic tissue. Stimulated monocytes acquired a myofibroblast-like phenotype with increased expression of collagen I (p<0.0001), fibronectin (p<0.05), and α smooth muscle actin (α-SMA) in comparison to untreated cells. Similarly, CD14 + monocytes exposed to dermal or cardiac fibroblasts acquired spindle shape and expressed higher levels of profibrotic genes. The process of monocyte-to-myofibroblast differentiation employed TGF-β/SMAD signalling. Blocking of the TGF-β receptor I and canonical SMAD-dependent pathway with inhibitors resulted in the abrogation of collagen I secretion by monocytes (p=0.002). CD14 + monocytes from SSc patients were characterised by higher secretion of CXCL10 (p<0.001), which was significantly decreased after cytokine stimulation (p<0.001). Additionally, a tendency towards higher secretion of CCL20, CCL22, Leukemia Inhibitory Factor and neurotrophin-3 was observed for SSc monocytes. Conclusions: Here we demonstrated the capability of peripheral blood monocytes to differentiate towards the functional myofibroblast phenotype, designating these cells as one of the potential sources of pathological tissue myofibroblasts in SSc. Additionally, these cells sustained pro-fibrotic cytokines secretion, highlighting their important regulatory functions in the fibrogenesis in SSc. Further studies of monocytes involvement in SSc might lead to novel treatment strategies. Disclosure of Interest: M. Rudnik: None declared, M. Stellato: None declared, V. Milleret: None declared, P. Błyszczuk: None declared, B. Maurer Grant/research support from: AbbVie, Protagen, EMDO, Novartis. Congress support from Pfizer, Roche, Actelion. Patent licensed: mir-29 for the treatment of systemic sclerosis, K. Klingel: None declared, J. Henes: None declared, K. Sotlar: None declared, M. Ehrbar: None declared, O. Distler Grant/research support from: Actelion, Bayer, Boehringer Ingelheim, Pfizer, Sanofi. Patent licensed: mir-29 for the treatment of systemic sclerosis, Consultant for: 4 D Science, Actelion, Active Biotec, Bayer, BiogenIdec, BMS, Boehringer Ingelheim, ChemomAb, EpiPharm, espeRare foundation, Genentech/Roche, GSK, Inventiva, Lilly, medac, Mepha, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Pfizer, Sanofi, Serodapharm, Sinoxa, Speakers bureau: AbbVie, iQone Healthcare, Mepha, G. Kania Grant/research support from: Bayer